Renal and survival benefits of seventeen prescribed Chinese herbal medicines against oxidative-inflammatory stress in systemic lupus erythematosus patients with chronic kidney disease: a real-world longitudinal study - Chen, Hsiao-Tien; Tung, Chien-Hsueh; Yu, Ben-Hui; Chang, Ching-Mao; Chen, Yi-Chun (Frontiers in Pharmacology, 2024)
Background: Systemic lupus erythematosus (SLE) significantly links to LN, a type of CKD with high mortality despite modern Western treatments. About 70% of SLE patients develop LN, and 30% advance to end-stage renal disease (ESRD). Concerns about glucocorticoid side effects and LN worsening due to oxidative stress prompt alternative treatment searches. In Taiwan, over 85% of SLE patients opt for complementary methods, especially Chinese herbal medicine (CHM). We pinpointed seventeen CHMs for SLE (PRCHMSLE) with antioxidative and anti-inflammatory properties from national health insurance data (2000-2017). Our primary aim was to assess their impact on renal and survival outcomes in SLE patients progressing to CKD (SLE-CKD), with a secondary focus on the risks of hospitalization and hyperkalemia. Methods: We established a propensity-matched cohort of 1188 patients with SLE-CKD, comprising 594 PRCHMSLE users and 594 nonusers. We employed Cox proportional hazards models and restricted mean survival time (RMST) analyses to assess the renal and survival outcomes of PRCHMSLE users. Moreover, we performed pooling and network analyses, specifically focusing on the renal effects linked to PRCHMSLE. Results: PRCHMSLE use was associated with decreased adjusted hazard ratios for ESRD (0.45; 95% confidence interval, 0.25-0.79, p=0.006), all-cause mortality (0.56; 0.43-0.75, p<0.0001), non-cardiovascular mortality (0.56; 0.42-0.75, p<0.0001), and hospitalization (0.72; 0.52-0.96, p=0.009). Hyperkalemia risk did not increase. Significant differences in RMST were observed: 0.57 years (95% confidence interval, 0.19-0.95, p=0.004) for ESRD, 1.22 years (0.63-1.82, p<0.0001) for all-cause mortality, and 1.21 years (0.62-1.80, p<0.0001) for non-cardiovascular mortality, favoring PRCHMSLE use. Notably renoprotective PRCHMSLE included Gan-Lu-Ying, Anemarrhena asphodeloides Bunge [Asparagaceae; Rhizoma Anemarrhenae] (Zhi-Mu), Rehmannia glutinosa (Gaertn.) DC. [Orobanchaceae; Radix Rehmanniae] (Sheng-Di-Huang), Jia-Wei-Xiao-Yao-San, and Paeonia suffruticosa Andr. [Paeoniaceae; Cortex Moutan] (Mu-Dan-Pi). Network analysis highlighted primary treatment strategies with central components like Liu-Wei-Di-Huang-Wan, Paeonia suffruticosa Andr. [Paeoniaceae; Cortex Moutan] (Mu-Dan-Pi), Anemarrhena asphodeloides Bunge [Asparagaceae; Rhizoma Anemarrhenae] (Zhi-Mu), Rehmannia glutinosa (Gaertn.) DC. [Orobanchaceae; Radix Rehmanniae] (Sheng-Di-Huang), and Zhi-Bai-Di-Huang-Wan. Conclusions: This work underscores the pronounced renal and survival benefits associated with the seventeen PRCHMSLE in the treatment of SLE-CKD, concurrently mitigating the risks of hospitalization and hyperkalemia. This highlights their potential as alternative treatment options for individuals with this condition.